Underlying factors of the impact of the mentoring process on women's career advancement - Seyed Mojtaba Mahmoudzadeh; Zohreh Dehdashti Shahrokh; Mehdi Yazdanshenas; Parvaneh Bahrami (مطالعات مدیریت بهبود و تحول, 2022)
The purpose of this study is to identify the underlying factors of the impact of the mentoring on women's career advancement in Tehran Municipality.The research method used in the study was a qualitative method with an exploratory nature that is performed using Constructivist Grounded Theory method. For this purpose, eighteen interviews were conducted and analyzed using a constructivist approach.The research population consists of specialists participating in the mentoring in Tehran Municipality. For sampling, Judgmental sampling was used and data from field studies were coded using grounded theory method that consisted of four stages of coding. The analysis of the findings shows that Underlying factors of the impact of mentoring on women's career advancement include eight categories Individual requirements, Mentor requirements, demographic requirements, mentor requirements, cultural requirements, extra-organizational requirements and interpersonal requirements. Implementing mentoring can help women's career advancement in organizations. In this regard, organizations must consider the requirements for proper implementation of mentoring and improvement of results.